The Experiential Path of Exercising Clinical Nursing Leadership Among Newly Graduated Nurses: An Interpretative Descriptive Study (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
Background: Western health care systems rely on the exercise of nursing competencies to ensure patient safety. Among them is clinical nursing leadership (CNL). Nurses are expected to demonstrate high level of CNL in their practice, regardless of the length of their experience. The literature provides an understanding of the development of this nursing competency, with landmarks of its exercise, but remains silent regarding the pathways of its exercise early in the career.Objectives: The aim of this interpretive qualitative descriptive study was to describe the experiential path of exercising CNL among newly graduated nurses (NGNs) in their first year of professional practice, including the identification of elements that facilitated or impeded its exercise, from their perspective. The conceptual framework guiding this study encompasses the development of clinical nursing expertise and the notion of individuation through life courses.Methods: Data were gathered from semi-structured interviews, lasting 45 to 60 minutes, with eight NGNs from one university hospital. All audio taped interviews were individually coded and analyzed according to a thematic content analysis method.Results: NGNs relayed five cumulative ways of exercising CNL within their first year of professional practice: 1) maintaining an optimal level of quality of their patient care; 2) collaboration and effective communication with the care team; 3) adopting the role of clinical preceptor; 4) professional involvement beyond the patient care; and 5) improving practices by consulting scientific evidence. Furthermore, these participants identified factors that facilitated or impeded their ability to exercise CNL in a 1-year trajectory. These factors fall into three categories: teams, shifts, and resources.Impact statement NGNs need to be supported by their nursing organizations to exercise their CNL during the first 12 months of professional practice. Our findings have the potential to guide strategies for supporting the exercise of this competency within the nursing practice.